Receding-Horizon Adaptive Control of Laser Beam Jitter - Tsuchiya, Nolan; Gibson, Steve; Tsu-Chin Tsao; Verhaegen, Michel (IEEE/ASME transactions on mechatronics, 2016)
This paper uses a new method for receding-horizon adaptive control to reduce laser beam jitter. The control scheme generates a control command derived from a receding-horizon performance index that involves predicted future values of an output disturbance. A recursive least-squares adaptive lattice filter performs the required prediction based on real-time measurements. In a laser beam steering experiment, the adaptive controller drives a micro mirror to cancel broadband disturbance and maintain the laser spot on an optical position sensor. Experimental results demonstrate the capability of the receding-horizon adaptive controller to incorporate frequency weighting to reduce sensitivity to plant modeling error at high frequencies.